Classical complement activation on human erythrocytes in subjects with systemic lupus erythematosus and a history of autoimmune hemolytic anemia. (September 2020) - Hair, Pamela; Goldman, Daniel W; Li, Jessica; Petri, Michelle; Krishna, Neel; Cunnion, Kenji
Introduction: Autoimmune hemolytic anemia (AIHA) is a serious manifestation of systemic lupus erythematosus (SLE) associated with significant morbidity and mortality. In order to more fully understand the causative pathways, we utilized sera from subjects with SLE and active AIHA, or a history of AIHA, to evaluate the classical complement pathway, anti-erythrocyte antibodies, and immune complexes. Methods: To evaluate antibody-mediated complement activation on the surface of erythrocytes, as occurs in AIHA, blood type O erythrocytes were incubated with sera from 19 subjects with SLE and a history of AIHA. Circulating anti-erythrocyte antibodies and immune complexes were measured with ELISA-based assays. Results: In total, 90% of subjects with SLE and a history of AIHA, but not active clinical hemolysis, had measurable anti-erythrocyte antibodies. Of those with anti-erythrocyte antibody, 53% demonstrated complement opsonization on the erythrocyte surface >twofold above negative control and 29% generated the anaphylatoxin C5a. Conclusions: For subjects with SLE and a history of AIHA, the persistence of circulating anti-erythrocyte antibodies and resultant erythrocyte complement opsonization and anaphylatoxin generation suggests the possibility that these complement effectors contribute to chronic morbidity and risk of AIHA relapse.